2014
DOI: 10.1177/1079063214557173
|View full text |Cite
|
Sign up to set email alerts
|

A Matter of Low Self-Control? Exploring Differences Between Child Pornography Possessors and Child Pornography Producers/Distributers Using Self-Control Theory

Abstract: This study examined the demographic and background characteristic differences between those arrested for child pornography (CP) possession (only), or CP production/distribution, or an attempted or completed sexual exploitation of a minor (SEM) that involved the Internet in some capacity within the context of self-control theory using data from the second wave of the National Juvenile Online Victimization Study (N-JOV2). Results indicate few demographic similarities, which thereby suggest these are largely hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 29 publications
2
34
0
Order By: Relevance
“…Based on Table 1, ICPOs are significantly more likely to be better educated, employed, and have higher incomes than contact offenders (Ly et al, 2016). Clevenger, Navarro, and Jasinski (2016) propose that being employed could indicate more self-control in online offenders. Clevenger et al (2016) concluded that ICPOs may be less likely to commit hands-on offenses because they have more self-control than online solicitors.…”
Section: Characteristics Of Icpos and Mixed Offendersmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on Table 1, ICPOs are significantly more likely to be better educated, employed, and have higher incomes than contact offenders (Ly et al, 2016). Clevenger, Navarro, and Jasinski (2016) propose that being employed could indicate more self-control in online offenders. Clevenger et al (2016) concluded that ICPOs may be less likely to commit hands-on offenses because they have more self-control than online solicitors.…”
Section: Characteristics Of Icpos and Mixed Offendersmentioning
confidence: 99%
“…Clevenger, Navarro, and Jasinski (2016) propose that being employed could indicate more self-control in online offenders. Clevenger et al (2016) concluded that ICPOs may be less likely to commit hands-on offenses because they have more self-control than online solicitors. However, ICPOs reported having less self-restraint when compared to online solicitors (Clevenger et al, 2016).…”
Section: Characteristics Of Icpos and Mixed Offendersmentioning
confidence: 99%
See 1 more Smart Citation
“…Although assessing the prevalence of child pornography is challenging, studies on arrested offenders are enlightening. For example, in a study focused on arrested online sexual offenders, nearly half of the perpetrators included in the sample (48%) engaged in the sexual solicitation of a minor (Clevenger, Navarro, & Jasinski, ). In terms of child pornography, most offenders solely possessed the offensive material (46%) whereas a smaller percentage produced and distributed it (6%; Clevenger et al, ).…”
Section: Cybersexual Exploitationmentioning
confidence: 99%
“…For example, in a study focused on arrested online sexual offenders, nearly half of the perpetrators included in the sample (48%) engaged in the sexual solicitation of a minor (Clevenger, Navarro, & Jasinski, ). In terms of child pornography, most offenders solely possessed the offensive material (46%) whereas a smaller percentage produced and distributed it (6%; Clevenger et al, ). In another study that utilized a community sample , a small percentage of men (9%) and women (3%) expressed desires indicative of being child pornographers (Wurtele, Simons, & Moreno, ).…”
Section: Cybersexual Exploitationmentioning
confidence: 99%